Extraction and Characterization of Coffee Oil From Instant-Coffee Waste (Jurnal Bahan Alam Terbarukan, 2019)
The higher demands of fossil energy usage are currently imbalance to its reserves. This issue will give a potency of fossil fuel scarcity that contributes on rising of its cost and disturbing economic stabilization in the future. It is desirable to find another resource which is sustainable and renewable to reduce the dependency on this resource. This study aimed to utilize the oil from instant coffee waste as biodiesel feedstocks. The coffee oil was extracted from instant-coffee waste by Soxhlet extractor and characterized its physical and chemical properties. The solvent extraction through the solid bed of coffee ground performed by five cycles interval using n-hexane as a solvent. Separation processing oil from its hydrocarbon solvent was in a rotary vacuum evaporator and the oil extract collected for further purposes. There was about 17.6% (on a dry weight basis) of coffee oil gained on 20 cycles of extraction. Analysis regarding its physicochemical properties reported that the crude oil has 0.89 g/mL of density, 43.82 mm2/s of kinematic viscosity, 44.47 mg KOH/g of acid value, and 176.40 mg KOH/g of saponification value. The fatty acids composition of the oil provided by GC-MS analyzer showed that unsaturated fatty acids contained, observed as trans-fatty acids rather than cis-fatty acids.